Evaluation of Algamix® and two drainage rates in sweet pepper (Capsicum annuum) grown under greenhouse conditions - Monge Pérez, José Eladio (2023)
The application of biostimulants and the use of various percentages of drainage can affect production in protected agriculture.  Researchers evaluated the effect of applying the biostimulant Algamix® (foliar, root, and control treatments) and two drainage rates (10 % and 30 %) on the yield and quality of sweet pepper cv. Nathalie grown under greenhouse conditions.  Evaluated variables were: plant height (cm), stem diameter (mm), number of fruits per plant, fruit weight (g), yield (ton/ha), and percentage of total soluble solids (°Brix).  The application of biostimulant did not produce statistically significant differences in any of the variables, except in the yield of third-quality fruits, where the plants that received the foliar application of biostimulant produced a lower yield, compared to the control.  Compared to plants with a 30 % drainage rate, plants with a 10 % rate showed:  a lower number of fruits per plant and a lower yield, in the case of first quality; a greater quantity of fruits per plant and a higher yield, in the case of third-quality; a lower weight of the fruit (total and first quality); and a lower percentage of total soluble solids in the fruit.  The application of biostimulant improved neither the yield nor the quality of sweet pepper, for which its use is not recommended under the conditions in which the study was carried out.  The use of a 30 % drainage rate is recommended in greenhouse-grown sweet pepper, as it produced the highest yield of first- quality fruit.